2016
DOI: 10.18203/2394-6040.ijcmph20162596
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of relationship between eating habits and body mass index of students in Mount Kenya University, Rwanda

Abstract: Background: Eating habits are a major concern among university students especially due to the transition from home environment where parents determine what to be eaten, to new environments where they or their peers choose the diet. Eating habits are considered determinants of health conditions and has been linked to death from Noncommunicable diseases. Methods: This cross-sectional study was conducted in school of Health Sciences at Mount Kenya University. A total of 630 students from entire school of health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…On the other hand, [35], found that, about two thirds of adolescents belonged to normal and underweight, and the last third of them were obese and overweight. These findings are in line with [24], who found that, almost of students had normal weight but there is a reasonably high occurrence of overweight among the students.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, [35], found that, about two thirds of adolescents belonged to normal and underweight, and the last third of them were obese and overweight. These findings are in line with [24], who found that, almost of students had normal weight but there is a reasonably high occurrence of overweight among the students.…”
Section: Discussionsupporting
confidence: 91%
“…Eating habits are a main concern amongst university students particularly due to the transition from home atmosphere where parents decide what to be eaten, to new environments where they or their peers select the diet. Eating habits are considered determinants of health status and has been related to death from Noncommunicable illness [24]. In this circumstance, university students signify an attractive type of consumer because on the one hand, they affected by the food utilization choices of their families, while on the other hand, they are starting to make self-determining food selections [25].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…This study finding is similar to the findings of the study done on university students in Malaysia (Gan et al, 2011). It is also partly in agreement with a report from a study conducted by Waweru and Marete (2016) on the relationship between eating habits and BMI of students in Mount Kenya University, Rwanda that showed the prevalence of underweight (14%) to be higher than that of obesity (1%) but lower than Table 3. Association between sugar and sweetened drinking habits and overweight and obesity among students in public and private schools in The Gambia, 2019.…”
Section: Discussionsupporting
confidence: 92%
“…High consumption of calorie foods among Omani adolescents did not prevent them from maintaining normal weight status (Kilani et al, 2013). The unhealthy dietary habit found among students in this study is typical of the student population in Africa such as in Cameroun (Waweru and Marete, 2016) and Nigeria (Otemuyiwa and Adewusi, 2012).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation